The early development of orange-spotted grouper Epinephelus coioides, (Hamilton, 1822) effects of salinity on egg hatching, yolk absorption and growth - Luna, Zaldy Odono (College of Fisheries, U. P. in the Visayas, 1998)
This study was conducted to determine the effect of different salinity levels on the early development, hatching rate, yolk absorption and larval growth of Epinepheluscoioides from newly-fertilized eggs up to the stage where yolk had been resorbed completely. The following treatments were used : Treatment I (0 ppt). Treatment II (10 ppt).Treatment III (15 ppt).Treatment IV (20 ppt.)Treatment V (25 ppt), Treatment VI (30 ppt), Treatment VII (35ppt), and Treatment VIII (40 ppt). Each treatment was replicated three times. Results showed that eggs developed was delayed by 1- 3 hr in low salinities (10, 15, 20, and 25 ppt) compared with those incubated at higher salinities (30, 35, and 40 ppt). The appearance f newly-hatchedlarvae in Treatment VIII, VII, VI and V was observed at 19, 20, 21, and 22 hr after fertilization respectively : but it was 23 and 24 hr for Treatments IV, III and II, respectively. At 40, 35, 30, and 25 ppt salinities, the hatching rates were 72, 65, 57, and 51% respectively ; while lower hatching rates of 43, 37, and 26% were observed at salinities, 20, 15, and 10 ppt, respectively. These results showed that higher salinities (40 and 35 ppt) gave the best hatching rates in these salinities may be attributed to the presence of high levels of physiological ions like CI, NA+, SO4, K+, Ca2+ and Mg2+ to the culture media.Larval body length, yolk and oil globule volumes varied significantly (P<0.01) in relation to salinity. The yolk was completely absorbed during (Time after Hatching-TAH). The newly-hatchedlarvae tolerated abrupt changes in salinity from 10 to 40 ppt. A significant difference (P<0.01) was observed on the rate of yolk absorption in all test salinities. The growth rate of yolk-saclarvae in all test salinities ranged from 0.086 to 0.103 mm/day at Day-01, from 0.113 to 0.125 mm/day at Day-02, and from 0.149to o.173 mm/day at Day-03. A significant differences(P<0.01) were obtained from all the treatments after the rearing period. The rates of abnormality in embryos and larvae were found higher at lower salinities as these wereaffected significantly (P<0.01) by rearing salinities. A significant difference (P<0.01) was observed on the survival of yolk-sac larvae in all test salinities. At higher salinities, the survival rates in Treatments VIII, VII and VI were 38.25, 39.23, and 41.97%, respectively ; while at lower salinities the survival rates were 48.09, 51.17, and 41.97% for Treatments V, IV, and Irespectively. Treatment III (15 ppt) had the highest survival of 63.46%. In this study, 15 ppt salinity gave better result in terms of high survival and growth rates for the yolk-sac larvae of E. coioides.